Optimizing Educator Performance at MIN 2 Bandung City Through the Application of Herzberg's Theory - Asri Sulastri; Mulyawan Safwandy Nugraha (al-Afkar, Journal For Islamic Studies, 2025)
Motivation is a strong desire that arises within a person. In Herzberg's motivation theory, there are two factors: motivational factors and maintenance factors (hygiene factors). Motivation factors consist of job satisfaction, appreciation, responsibility, achievement, and job satisfaction. Meanwhile, maintenance factors include policies and administration, supervision, relationships with coworkers, working conditions, and salary or benefits. Motivation factors play a role in fostering work enthusiasm among educators. In addition, good relationships with coworkers and good working conditions also affect work performance. This study aims to identify the extent to which motivation can influence the work performance of educators at MIN 2 Bandung City when reviewed using Herzberg's motivation theory. The method used in this study was qualitative, with observations at the target madrasah or school, interviews with educators, and documentation in the form of images as additional data. The results revealed that the educators' motivation was built from within each individual. While some of Herzberg's maintenance factors are considered influential, many educators at MIN 2 Bandung City have their own unique motivations to become educators for the younger generation.